2017
DOI: 10.1097/md.0000000000006108
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined oral sucrose and nonnutritive sucking (NNS) on procedural pain of NICU newborns, 2001 to 2016

Abstract: Background:Both oral sucrose (OS) and nonnutritive sucking (NNS) are effective nonpharmacological methods to alleviate procedures pain in neonatal intensive care unit (NICU) newborns when they were used alone, but the combined effect of OS+NNS remains controversial. So, we conducted this study to evaluate the efficiency of NNS combined with oral sucrose on pain relief in NICU newborns undergoing painful procedures.Methods:We searched PubMed, Ovid (Medline), Embase (Medline), Cochrane Central Library, and other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 50 publications
2
32
1
3
Order By: Relevance
“…[22] However, we used single OS dose with acceptable effect. Although studies reported that, combined pacifier and OS lowered O 2 saturation fluctuations and heart rate in comparison to OS alone, [23] a meta-analysis showed that, combined OS and pacifier did not differ signifi-cantly in lowering the risk of bradycardia, tachycardia, and O 2 desaturations incidence between the 2 groups [24] which is not the case in the current study.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…[22] However, we used single OS dose with acceptable effect. Although studies reported that, combined pacifier and OS lowered O 2 saturation fluctuations and heart rate in comparison to OS alone, [23] a meta-analysis showed that, combined OS and pacifier did not differ signifi-cantly in lowering the risk of bradycardia, tachycardia, and O 2 desaturations incidence between the 2 groups [24] which is not the case in the current study.…”
Section: Discussioncontrasting
confidence: 81%
“…They concluded that, the combination is effective not only for management but also for better prevention of procedure related pain among NICU newborns. [24] The combination of NNS with OS provided better pain relief during repeated painful procedures than each of them alone. The effect of NNS was similar to that of OS on repeated procedural pain.…”
Section: Discussionmentioning
confidence: 98%
“…Non-nutritive sucking often associated with the use of 25% glucose can be considered as care technology, which provides a relief for the premature NB pain and contributes to its quality survival (31) . Scientific evidence found in a meta-analysis corroborates this statement (32) . Non-nutritive sucking inhibits hyperactivity, relieves NB discomfort, and minimizes pain when undergoing acute painful procedures.…”
Section: Discussionsupporting
confidence: 75%
“…Swaddling and NNS were used in Norway, but not in South Africa. Such measures may have synergistic effects with sucrose during painful procedures in newborn infants , potentially related to different pathways for pain relief. Sucrose works, at least partly, by releasing endogenous opioids in the central nervous system , whereas NNS alleviates pain through nonopioid mechanisms .…”
Section: Discussionmentioning
confidence: 99%